Biomimetic Architecture Towards Bio Inspired Adaptive Envelopes: In Case of Plant Inspired Concept Generation (International Journal of Built Environment and Sustainability, 2021)
In recent decades, the value of architecture become more due to its importance for reducing detrimental effects on the environment and natural capital. To minimize the building's impact on the environment, architectural designs should be highly incorporated into the environment rather than behaving as a separate element focused on a single issue. To address this problem, different methods and design approaches have been introduced. However, exploring the natural solutions for survival can provide invaluable data which can address the human-caused problems. Throughout decades, nature has been survived and evolved. Biological solutions due to their adaptability and multi-functionality are great source of inspiration. This article with help of content analysis method aims to review the concept of biomimetic design in architecture. And proposes plant-inspired solutions for envelope design which can play significant role on buildings’ energy efficiency. Thus, the plant-inspired concepts to be integrated on adaptive envelopes were studied. And a framework for concept generation introduced. Furthermore, a case study on an existing building envelope in the Mediterranean climate region presented and two plant-inspired techniques proposed and conceptually applied.